Haiti Acute and Emergency Care Conference: descriptive analysis of an acute care continuing medical education program - Lia I Losonczy; Sarah Williams; Alfred Papali; Corey A Costantino; L Nathalie Colas; Bhavesh M Patel; Donald F Zimmer; Shannon R Olwine; Zena Davidson; John W Wilson; Michael T McCurdy; Marc E Augustin; et al. (Journal of Global Health Reports)
# Background